"Death with boots on": Challenges faced by elderly farmers in the process of retirement and family succession (Desenvolvimento em Questão, 2024)
The rural population and the managers of agricultural production units are aging and the generational renewal in the countryside is finding it difficult to be carried out. One of the central aspects of this difficulty lies in the resistance of older farmers to hand over property management to younger ones. The objective of this study was to analyze and understand the weaknesses and problems faced by elderly farmers in the face of the succession process and their withdrawal from the management of rural properties. Methodologically, bibliometric research was carried out, followed by an in-depth systematic review. Scopus was used as a database considering the following keywords "retirement" AND "succession" AND "farm". From the search and refinement of the documents, 34 documents resulted to be analyzed. It was found that older farmers have difficulties leaving the management and activities of the rural property, that is, they do not retire. Such problems exist, above all, because of the symbolic capital that the rural property represents for the older farmer and the negative social weight or judgment for those who withdraw because socially there is a consensus that good farmers do not retire. Such behavior has negative consequences in the context of the succession process, rural properties, and the development of agriculture. Government assistance through the payment of subsidies to elderly farmers or young successors would help with the intergenerational transfer of agriculture as well as semi-retirement.
Keywords: Resistance to retirement; succession in agriculture; bibliometric analysis; belonging